Biochemistry and Molecular Biology PBL Cases - Marshall Anderson (Association of American Medical Colleges, 2006)
Abstract This resource is a collection of six problem-based learning (PBL) cases suitable for a biochemistry and molecular biology course taken by first- or second-year medical students. The six cases cover the following topics: (1) hormonal regulation of carbohydrate metabolism, (2) protein structure and function in a case of alpha-1 antitrypsin deficiency, (3) a common inborn error of metabolism in which there is an inability to metabolize medium-chain fatty acids, resulting in severe hypoglycemia, (4) a common inborn error in metabolism in which the patient is unable to convert the amino acid phenylalanine to tyrosine, leading to mental retardation, (5) the current state of gene therapy, and (6) DNA replication and its importance in disease processes, such as cancer. The cases are presented to students using the PBL progressive discovery method. The cases help the students to understand: (1) the importance of maintaining glucose homeostasis, (2) the important relationship between carbohydrate and lipid metabolism, and how a genetic defect in either process can be either benign or life threatening, (3) the complexities of disease processes, (4) the importance of nutritional therapy and patient/family education as it relates to the treatment of pediatric diseases, (5) the importance of diagnostic clinical testing and neonatal screening, and (6) the importance of basic science as the foundation of the clinical sciences.